Enantioselective synthesis of diarylcyclopropanecarboaldehydes by organocatalysis. Issue 51 (21st December 2016) - Chen, Xuyun; Yu, Yang; Liao, Ziyang; Li, Hao; Wang, Wei
Graphical abstract: Highlights: Chiral trisubstituted diarylcyclopropanecarboaldehydes have been synthesized by organocatalysis. The enantioselectivities of trisubstituted diarylcyclopropanecarboaldehydes are very high. The reactions can be proceeded under the mild conditions. Abstract: An efficient synthetic method for chiral trisubstituted diarylcyclopropanecarboaldehydes has been developed from substituted benzyl chloride and α, β-unsaturated aldehydes. The reactions were catalyzed by chiral amine catalyst under mild condition to afford the chiral diarylcyclopropanecarboaldehydes in good to high yields and up to excellent enantioselectivities.